Srumbung Gunung Peace Creative Tourism Village: An Effort to Build Interfaith Peace Through Tourism - Supratikno, Agus; Kartika Hudiono, Rini; Maria, Evi; Suharyadi (Pandawan, 2022)
This article discusses the Peace Creative Tourism Village as a peaceful tourism destination to build peace between religions and beliefs in Indonesia. This study is motivated by the rise of identity politics after the collapse of the New Order in 1998. The rise of identity politics has triggered several inter-ethnic and religious conflicts in several regions in Indonesia. Conflicts between the Dayak tribes and Madurese migrants occurred in Kalimantan in early February 2001, Christian and Muslim conflicts in Posso in 1998, and Ambon in 1999. The state has made various efforts to maintain peace between ethnic and religions in Indonesia, but intolerance, even inter-ethnic and religious conflicts, still occur in plural Indonesia. This study discusses an alternative effort to build peace between religions and beliefs through tourist destinations. This research uses a case study qualitative method. This study found that the Peace Creative Tourism Village of Srumbung Mountain, with its tour packages: peace education, live-in, and traditional culinary and cultural festivals, can be a local contribution to building peace between religions and beliefs in Indonesia.